Simple and Accurate Instrumentation Device to Detect Loose-End Defective Cigarettes - Dista Yoel Tadeus; Fakhruddin Mangkusasmito; Ari Bawono Putranto; Muhamad Ramzy Raihan (Ultima Computing : Jurnal Sistem Komputer, 2023)
Loose-end defect on the tip of the cigarette is a common problem found on production lines. Large companies use computerized sophisticated machines to detect and reject it automatically. However, the same solution can not be implemented in small or home industries because the investment cost is too high. This paper presents the development of simple electronic instrumentation to detect loose-end defects in cigarettes. It relies on the signal acquisition of a photoelectric transceiver mechanism that is converted and processed digitally to relatively quantify the difference between the good and defect. Motor-driven cigarette rotator device was built specially to test the performance of the instrumentation system. Loose-end defects are made artificially by removing 0.2 gr tobacco from the tip of a normal cigarette. The average quantifying relative value was found above 58.5%, this indicates that the system has good contrast properties. At the speed of 10,000 cigarettes/min, the average accuracy is 90.5%, and at 17,500 cigarettes/min, the average accuracy is 65.3%.